Venovenous extracorporeal CO2 removal to support ultraprotective ventilation in moderate-severe acute respiratory distress syndrome: A systematic review and meta-analysis of the literature. (July 2023) - Worku, Elliott; Brodie, Daniel; Ling, Ryan Ruiyang; Ramanathan, Kollengode; Combes, Alain; Shekar, Kiran
Background: A strategy that limits tidal volumes and inspiratory pressures, improves outcomes in patients with the acute respiratory distress syndrome (ARDS). Extracorporeal carbon dioxide removal (ECCO2 R) may facilitate ultra-protective ventilation. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of venovenous ECCO2 R in supporting ultra-protective ventilation in moderate-to-severe ARDS. Methods: MEDLINE and EMBASE were interrogated for studies (2000–2021) reporting venovenous ECCO2 R use in patients with moderate-to-severe ARDS. Studies reporting ≥10 adult patients in English language journals were included. Ventilatory parameters after 24 h of initiating ECCO2 R, device characteristics, and safety outcomes were collected. The primary outcome measure was the change in driving pressure at 24 h of ECCO2 R therapy in relation to baseline. Secondary outcomes included change in tidal volume, gas exchange, and safety data. Results: Ten studies reporting 421 patients (PaO2 :FiO2 141.03 mmHg) were included. Extracorporeal blood flow rates ranged from 0.35-1.5 L/min. Random effects modelling indicated a 3.56 cmH2 O reduction (95%-CI: 3.22–3.91) in driving pressure from baseline ( p < .001) and a 1.89 mL/kg (95%-CI: 1.75–2.02, p < .001) reduction in tidal volume. Oxygenation, respiratory rate and PEEP remained unchanged. No significant interactions between driving pressure reduction and baseline driving pressure, partial pressure of arterial carbon dioxide or PaO2 :FiO2 ratio were identified in metaregression analysis. Bleeding and haemolysis were the commonest complications of therapy. Conclusions: Venovenous ECCO2 R permitted significant reductions in ∆P in patients with moderate-to-severe ARDS. Heterogeneity amongst studies and devices, a paucity of randomised controlled trials, and variable safety reporting calls for standardisation of outcome reporting. Prospective evaluation of optimal device operation and anticoagulation in high quality studies is required before further recommendations can be made.